2016
DOI: 10.1002/jrs.4881
|View full text |Cite
|
Sign up to set email alerts
|

OctTES/TEOS system for hybrid coatings: real-time monitoring of the hydrolysis and condensation by Raman spectroscopy

Abstract: The hybrid organic–inorganic system Tetra‐ethyl‐ortho‐silicate functionalized with Octyl‐triethoxy‐silane, studied as protective coating for the preservation of historical glasses from the environmental weathering agents, has been characterized by Raman spectroscopy by monitoring the sol‐gel reactions over time through characteristic features in the spectrum. In particular, for the hydrolysis reaction the disappearance of the 653 cm−1 (Si‐O symmetric breathing) and 810 cm−1 (CH2 rocking in Si‐alkoxides) peaks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…Different catalysts, such as ammonia, were used to improve the polymerization process to prepare monodisperse nanoparticles (Stöber method) [36,42,43,50,51,52]. Mineral acids, such as HCl [30,37,53,54,55,56,57,58], phosphoric acid [38], and hydrofluoric acid [59], as well as organic acids, such as acetic acid [2,23,26,45,60,61,62,63], chloroacetic acid [24], p -toluene sulphonic acid [22], and methane sulphonic acid [21], were also used. Researches also looked at the use of other organic compounds, such as tin alkyl esters [24,28], while boron-based catalysts were used to overcome the toxicity of the tin compounds.…”
Section: Hydrolysis and Early Stage Condensationmentioning
confidence: 99%
“…Different catalysts, such as ammonia, were used to improve the polymerization process to prepare monodisperse nanoparticles (Stöber method) [36,42,43,50,51,52]. Mineral acids, such as HCl [30,37,53,54,55,56,57,58], phosphoric acid [38], and hydrofluoric acid [59], as well as organic acids, such as acetic acid [2,23,26,45,60,61,62,63], chloroacetic acid [24], p -toluene sulphonic acid [22], and methane sulphonic acid [21], were also used. Researches also looked at the use of other organic compounds, such as tin alkyl esters [24,28], while boron-based catalysts were used to overcome the toxicity of the tin compounds.…”
Section: Hydrolysis and Early Stage Condensationmentioning
confidence: 99%
“…Keeping industrial upscaling in mind, one must be able to produce a coating precursor in a relatively short time-span, which can be conserved for longer times. Raman spectroscopy has proven to be a valuable technique to monitor the condensation species of silicon-based sol-gel reactions [ 28 , 29 , 30 ]. This technique was used to follow the condensation reaction over time.…”
Section: Resultsmentioning
confidence: 99%
“…de Ferri et al used the hybrid organic‐inorganic system tetra‐ethyl‐ortho‐silicate functionalized with octyltriethoxysilane as a protective coating for the preservation of historical glasses from environmental weathering agents. This coating has been characterized by Raman spectroscopy by monitoring the sol–gel reactions over time through characteristic features in the spectrum . Franca de Sa and co‐workers have provided new insight into polyurethane foam deterioration through the use of Raman microscopy for the evaluation of long‐term storage conditions.…”
Section: Special Raman Techniques and Methodsmentioning
confidence: 99%
“…This coating has been characterized by Raman spectroscopy by monitoring the sol-gel reactions over time through characteristic features in the spectrum. [178] Franca de Sa and co-workers have provided new insight into polyurethane foam deterioration through the use of Raman microscopy for the evaluation of long-term storage conditions. They found that open-air storage proved to be the most harmful condition, while anoxic storage showed the best results.…”
Section: New Techniquesmentioning
confidence: 99%